A Comparative Study of Dorsal Buccal Mucosa Graft Substitution Urethroplasty by Dorsal Urethrotomy Approach versus Ventral Sagittal Urethrotomy Approach. (30th September 2013) - Pahwa, Mrinal; Gupta, Sanjeev; Pahwa, Mayank; Jain, Brig D. K.; Gupta, Manu
Abstract : Objectives . To compare the outcome of dorsal buccal mucosal graft (BMG) substitution urethroplasty by dorsal urethrotomy approach with ventral urethrotomy approach in management of stricture urethra. Methods and Materials . A total of 40 patients who underwent dorsal BMG substitution urethroplasty were randomized into two groups. 20 patients underwent dorsal onlay BMG urethroplasty as described by Barbagli, and the other 20 patients underwent dorsal BMG urethroplasty by ventral urethrotomy as described by Asopa. Operative time, success rate, satisfaction rate, and complications were compared between the two groups. Mean follow-up was 12 months (6–24 months). Results . Ventral urethrotomy group had considerably lesser operative time although the difference was not statistically significant. Patients in dorsal group had mean maximum flow rate of 19.6 mL/min and mean residual urine of 27 mL, whereas ventral group had a mean maximum flow rate of 18.8 and residual urine of 32 mL. Eighteen out of twenty patients voided well in each group, and postoperative imaging study in these patients showed a good lumen with no evidence of leak or extravasation. Conclusion . Though ventral sagittal urethrotomy preserves the blood supply of urethra and intraoperative time was less than dorsal urethrotomy technique, there was no statistically significant difference in final outcome using either technique.